2008
DOI: 10.1007/s10532-008-9195-1
|View full text |Cite
|
Sign up to set email alerts
|

Cosubstrate independent mineralization of hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) by a Desulfovibrio species under anaerobic conditions

Abstract: Past handling practices associated with the manufacturing and processing of the high explosive hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) has resulted in extensive environmental contamination. In-situ biodegradation is a promising technology for remediating RDX contaminated sites but often relies on the addition of a cosubstrate. A sulfate-reducing bacterium isolated from an RDX-degrading enrichment culture was studied for its ability to grow on RDX as a sole source of carbon and nitrogen and for its abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…RDX can be biodegraded by a range of both anaerobic (Adrian and Sutherland 1999;Arnett and Adrian 2009;Fuller et al 2009;Hawari et al 2001;Zhang and Hughes 2003;Zhao et al 2004) and aerobic bacteria (Bernstein et al 2011;Fournier et al 2002;Fuller et al 2010a;Seth-Smith et al 2002;Thompson et al 2005). In situ anaerobic bioremediation of RDX (and other explosives) has been demonstrated at several sites (Hatzinger and Lippincott 2012;Michalsen et al 2013;Newell 2008;Wade et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…RDX can be biodegraded by a range of both anaerobic (Adrian and Sutherland 1999;Arnett and Adrian 2009;Fuller et al 2009;Hawari et al 2001;Zhang and Hughes 2003;Zhao et al 2004) and aerobic bacteria (Bernstein et al 2011;Fournier et al 2002;Fuller et al 2010a;Seth-Smith et al 2002;Thompson et al 2005). In situ anaerobic bioremediation of RDX (and other explosives) has been demonstrated at several sites (Hatzinger and Lippincott 2012;Michalsen et al 2013;Newell 2008;Wade et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic degradation proceeds via two single-electron transfer steps resulting in sequential denitration (2 NO 2 Ϫ removed) followed by ring cleavage and production of 4-nitro-2,4-diazabutanal (NDAB) (pathway C) (7). Some bacteria are able to utilize RDX as a nitrogen source (13)(14)(15), and at least one sulfate-reducing culture that is able to utilize RDX as a sole source of carbon, nitrogen, and energy has been isolated (16).…”
mentioning
confidence: 99%
“…It could further be concluded that RDX is capable acting as electron acceptor as well as electron donor in the absence of suitable exogenous donors. A previous study also showed that a sulfate‐reducing bacterium could degrade RDX in 63 days when incubated with RDX as sole carbon source 21…”
Section: Resultsmentioning
confidence: 91%